The Information and Communication Technologies, Learning and Knowledge Technologies and Technologies for Empowerment and Participation as Tools to Support the University Teachers of the XXI Century - John Granados Romero; Raúl López Fernández; Raidell Avello Martínez; Diego Luna Álvarez; Enrique Luna Álvarez; Walter Luna Álvarez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
The learning environment has suffered major transformations with the rapid development of the information and communications technologies; in this context the concept of learning and knowledge technologies and technologies for the empowerment and participation emerges. This paper aims at contributing to the reflection on the use of information and communication technologies that must be continually made in education, especially among teachers of the 21st century University. As main result, some comments on the digital competence of students of the 21st century are included. Although it has been demonstrated that these technologies are a social phenomenon of great significance that has changed the lives of millions of people, it has also been recognized that their impact on education is far from their potential.